Evaluation of C Reactive Protein and Uric Acid/Creatinine Ratio as Biomarkers in the Assessment of COPD Patients Attending a Tertiary Care Centre of Tripura, North Eastern India - Sharadia Majumder; Partha Sarathi Pal; Anishim Rokhum; Subhraneel Paul; Matrujyoti Pattnaik (International Journal of Health Sciences and Research, 2026)
Background: Chronic obstructive pulmonary disease (COPD) is a major global health burden, with systemic inflammation and oxidative stress contributing to its progression. C‑reactive protein (CRP) and the uric acid/creatinine ratio (UCR) have emerged as promising biomarkers for disease monitoring. Objective: To evaluate CRP and UCR levels among COPD patients admitted to a tertiary care centre in Tripura, North‑Eastern India, and to assess their correlation with clinical severity and recovery. Methods: A descriptive cross‑sectional study was conducted on 150 COPD patients admitted to Agartala Government Medical College & GBP Hospital. Serum CRP, uric acid, and creatinine were measured using standard biochemical assays. Comparative analyses were performed between admission and discharge values, with subgroup analyses by age, gender, occupation, and socio‑economic status. Results: Mean CRP levels declined significantly from 11.34 ± 4.35 mg/L at admission to 2.35 ± 0.85 mg/L at discharge (p< 0.001). Similarly, UCR decreased from 5.45 ± 1.74 to 4.78 ± 1.04 (p< 0.001). Elevated CRP was consistently associated with systemic inflammation, while higher UCR values correlated with hypoxemia and socio‑economic deprivation. No significant correlations were observed between CRP and UCR, underscoring biomarker heterogeneity. Conclusion: CRP and UCR are cost‑effective, accessible biomarkers that reflect systemic inflammation and oxidative stress in COPD. Their significant reduction during hospitalisation highlights their utility in monitoring therapeutic response and disease stability. Region‑specific validation supports their relevance for resource‑limited settings such as Tripura. Key words: Chronic obstructive pulmonary disease, C reactive protein, Uric acid/creatinine ratio, Biomarkers, Correlation, Tripura